Potential of the Cerrado Sensu Stricto arborous-arbustive structure for medical purposes (Research, Society and Development, 2021)
The Cerrado vegetation has high biodiversity and traditional and scientific knowledge about plants for medicinal purposes is important in consolidating therapeutic use, since they have been used in the treatment and cure of diseases for thousands of years. Based on the relevance of the theme, this study aims to evaluate the medicinal potential of species of plants in the arboreal-shrub stratum in a cerrado sensu stricto area. For this, a floristic-phytosociological survey was carried out in the conservation area of ​​the Planaltina campus of the Federal Institute of Brasília (IFB). In each sampled plot, all tree-shrub individuals with DAB (diameter taken at 30 cm from the base level) and DBH (diameter at breast height) equal to or greater than 5 cm and total height (Ht) were identified and measured. 943 individuals were identified, from 70 species, 34 botanical families in 56 genera. After phytosociological analysis of the sampled community, the 10 selected species of greater ecological relevance and thus a bibliographic survey was carried out in order to analyze the potential of these species for medicinal purposes. It was found that 90% of the most important species in the importance value index in the Parque Agricola Colégio Agrícola de Brasília, are of medicinal use consecrated by literature and traditional knowledge.